2019
DOI: 10.4322/2526-8910.ctoao1843
|View full text |Cite
|
Sign up to set email alerts
|

A relação entre emoção expressa e variáveis sociodemográficas, estresse precoce e sintomas de estresse em cuidadores informais de pessoas com transtornos mentais

Abstract: Introduction: Changes resulting in Brazilian psychiatric reform brought people with mental disorders closer to their families, who became responsible for the offer of care. Objective: The aim of this study was to investigate the expressed emotion, the early stress, and the stress symptoms among informal caregivers of people with mental disorders at the time of psychiatric hospitalization. Method: 112 caregivers participated. Four instruments were used to collect data: socio-demographic questionnaire, Family Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Several research studies conducted in Sri Lanka and the Netherlands have revealed that individuals who provide care for individuals with mental disorders tend to experience elevated levels of depressive symptoms and heightened caregiver strain [66,67]. In a similar vein, research conducted in Brazil and Spain has revealed that caregivers of individuals with mental disorders demonstrated elevated levels of emotion expressed and experienced significant levels of stress [68,69].…”
Section: Discussionmentioning
confidence: 97%
“…Several research studies conducted in Sri Lanka and the Netherlands have revealed that individuals who provide care for individuals with mental disorders tend to experience elevated levels of depressive symptoms and heightened caregiver strain [66,67]. In a similar vein, research conducted in Brazil and Spain has revealed that caregivers of individuals with mental disorders demonstrated elevated levels of emotion expressed and experienced significant levels of stress [68,69].…”
Section: Discussionmentioning
confidence: 97%
“…Psychoeducational research has an effect on reducing caregiver burden in schizophrenia patients. Psychoeducation is conducted, some using films and modules, but it's not specific to the care of auditory hallucinations (Araujo & Pedroso, 2019;Begam & Baruah, 2020).…”
Section: Introductionmentioning
confidence: 99%